Pengaruh Penggunaan Media Flashcard terhadap Efektivitas Pembelajaran Siswa Kelas III SD Negeri Kedungpane 02 - Dea Laila Puspita Sari; Alvina Meissy Gwenda Putri; Alsya Nabilla Azzarin; Betalis Cahyaningrum; Rina Nuraeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the effect of using flashcard media on the learning effectiveness of third-grade students at SD Negeri Kedungpane 02. The research was motivated by low student motivation, limited participation, and insufficient conceptual understanding caused by monotonous teaching methods. This study employed a descriptive qualitative metode with data collected through participatory observation, in-depth interviews, and document analysis. Data were analyzed using an inductive process involving reduction, presentation, and conclusion drawing. The results show that the use of flashcards increases students’ learning motivation, active participation, and interaction during classroom activities. Flashcards also enhance conceptual understanding through clear visual representations and strengthen memory retention through visual repetition. Moreover, positive behavioral changes were observed, including improved focus, greater confidence, and better readiness to engage in learning. Therefore, flashcard media are proven to be effective interactive tools for reducing learning fatigue and improving learning quality. Future research is recommended to explore the use of digital flashcards and apply the media to other subjects or grade levels.